Effect of occlusion style resistance training on the maximum strength of the lower limbs of soccer players - Zuheer Hassan, Ali (International Journal of Psychosocial Rehabilitation, 2020)
The current study investigates the role and effect of occlusion style resistance training among young soccer players, as well as its effect on the development of physical abilities in the lower limbs of the two men. The researcher noticed a big problem that football players suffer from when using resistance exercises with weights during the competitive season, as these high-intensity exercises and large repetitions constitute additional burdens that may exceed the capabilities of young players, which leads to the phenomenon of overload and functional stress and consequently injury. The avoidance of this phenomenon and the use of modern scientific methods in the number of training doses and taking into account the duration of work and rest usually achieve a full recovery. Among the modern methods are exercises to restrict blood flow to working muscles, and it aims to develop muscle properties and increase muscle mass and strength with an intensity that does not exceed (50% of the MR-1), and the experimental approach was used for its suitability and the nature of the research, as the research community was chosen in a random way of their number (20) Player, the researcher concluded that the use of this method, according to stratigraphy exercises, effectively contributed to the development of horizontal and vertical jumping for soccer players .